The Future Nexus of the Brahmaputra River Basin : Climate, Water, Energy and Food Trajectories - Yang, Y.C. Ethan; Wi, Sungwook; Ray, Patrick A.; Brown, Casey M.; Khalil, Abedalrazq F. (Elsevier, 2016)
Advance knowledge of conflicting trajectories of water–energy–food (WEF) nexus is highly relevant for water policy and planning, especially for basins that cross national boundaries. The Brahmaputra River Basin in South Asia, home for 130 million people, is such a basin. Development of new hydropower projects, upstream water diversions and possible climate changes introduce concerns among riparian countries about future water supply for energy and food production in the basin. This study presents a new hydro-economic water system model of the basin coupled with ex post scenario analysis under the “nexus thinking” concept to identify and illustrate where development paths are in conflict. Results indicate that the ability of future development to remain free of conflict hinges mostly on the amount of precipitation falling in the basin in the future. Uncertain future precipitation along with uncertain future temperature and the unknown amount of upstream water diversion combine to strongly influence future water, energy and food production in the basin. Specifically, decreases in precipitation coupled with large upstream diversions (e.g., diversion in the territory of China) would leave one or more riparian countries unable to secure enough water to produce their desired energy and food. Future climate projected by General Circulation Models suggest a warmer and wetter climate condition in the region, which is associated with an increase in streamflow and easing of conflicts at the WEF nexus in the basin. The methodology presented here is expected to be generally useful for diagnosing the conditions that may cause water resources development goals to not be achieved due to either changes in climate or water use among competing users.